CRUDE BIODIESEL SYNTHESIS FROM RUBBER SEED OIL - Doni Rahmat Wicakso; Anniy Nurin Najma; Diah Ayu Retnowati (Konversi, 2018)
Abstract-Biodiesel is a diesel engine fuel made from oil containing triglycerides as well as rubber seed oil. This research  aims to study how the extraction process of rubber seed oil, to know the effect of crude biodiesel manufacturing process by transesterification and esterification-transesterification and the addition of different catalysts on the transesterification process of crude biodiesel produced. Esterification process use H2SO4 catalyst and transesterification process use KOH and NaOH catalyst. The process of making crude biodiesel done by transesterification and can also by the merging of esterification-transesterification process. Based on this research, yield of crude biodiesel produced by transesterfication and esterification-transesterification by using NaOH catalyst is 38% and 75,6%, while yielded by KOH catalyst is 22,5% and 80%. While the acid number obtained from the transesterification process and esterification-transesterification using KOH catalyst is the same that is 1.33 and for the NaOH catalyst is 1,83 and 1,68. Saponification number obtained from both processes using KOH catalysts were 24,68 and 26,37 and for NaOH catalysts were 18,51 and 20,20.  Keywords: Rubber seed oil, crude biodiesel, acid number, saponification number.